CPEC and Healthcare Benefits - Muzammil Irshad (The International Journal of Frontier Sciences, 2017)
China-Pakistan Economic Corridor (CPEC) is a bond of bilateral cooperation between China and Pakistan to enhance economic growth of both the countries. As far as Pakistan is concerned, CPEC is one of the supreme strategies to modernize Pakistani infrastructure and to empower Pakistani economic growth in terms of transportation, energy, and numerous industrial reforms. Economic growth is considered a determinant of population health. It has been noted, “Wealthier nations are healthier nations” as they spend more on preventive medicine and on healthcare delivery. Hence, economic gains from CPEC development can flow into health gains as well.